The First Reported Foodborne Botulism Outbreak in Riyadh, Saudi Arabia: Lessons Learned - Nadeem Gul Dar; Sarah H. Alfaraj; Khulood Naser Alboqmy; Nazia Khanum; Faleh Alshakrah; Hassan Abdallah; Mohammad Hosni Badawi; Ohoud Mohammed Alharbi; Khadijh Ahmed Alshiekh; Abdullah M Alsallum; Ahmed Hassan Shrahili; Zeidan A Zeidan; et al. (Springer, 2024)
Abstract Background Botulism has not been previously reported in the Kingdom of Saudi Arabia. This rare and sometimes fatal foodborne illness is caused by neurotoxins and primarily results from consuming home-canned fruits, vegetables, dairy, and seafood products & it can lead to paralysis. Objective The purpose of this study was to evaluate the clinical features of patients who developed botulism in Riyadh in 2024 after consuming mayonnaise from a well-known local chain of restaurants in Riyadh, Saudi Arabia. Methods We conducted a retrospective analysis of medical records and interviewed patients or their attendants for all hospitalized cases of foodborne botulism at Riyadh First Health Cluster. For each patient, a standard case report form was completed, containing information on demographics, clinical aspects, botulinum test results, and type of exposure. Descriptive statistics were applied to assess the data. During the outbreak, nineteen patients with foodborne diseases were admitted to Riyadh First Health Cluster Hospitals. Following thorough physical examinations, botulism was suspected in each case. Results Eight of the 19 suspected foodborne illness patients fully satisfied the botulism case definition requirements set forth by the Saudi Arabian Public Health Authority (Weqaya). Among these eight patients, 2 (25%) were male and 6 (75%) were female, with a mean age of 23.25 ± 9.29 years (range: 12-38 years). The incubation period for our patients was 36.25 ± 26.26 h. Notable symptoms included dysphagia in all eight patients (100%), dysarthria, generalized weakness, nausea and vomiting in seven patients (88%), diplopia in four patients (50%), and stomach discomfort in three patients (38%). Of the eight cases, six required intubation, one mimicked brain death, and two were stable. The presence of Clostridium botulinum spores as the cause of the outbreak was confirmed by detecting botulinum spores in contaminated food. Conclusion Diplopia and dysarthria were the most common early sign of botulism. Early manifestations may include respiratory symptoms without any musculoskeletal symptoms. or nausea, vomiting and disorientation.